2010
DOI: 10.1037/a0018991
|View full text |Cite
|
Sign up to set email alerts
|

A vowel is a vowel: Generalizing newly learned phonotactic constraints to new contexts.

Abstract: Adults can learn novel phonotactic constraints from brief listening experience. We investigated the representations underlying phonotactic learning by testing generalization to syllables containing new vowels. Adults heard consonant-vowel-consonant (CVC) study syllables in which particular consonants were artificially restricted to onset or coda position (e.g., /f/ is an onset, /s/ is a coda). Subjects were quicker to repeat novel constraint-following (legal) than constraint-violating (illegal) test syllables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 42 publications
(70 reference statements)
7
42
0
Order By: Relevance
“…First, we explicitly trained participants to pay attention to semantic roles and provided extensive instructions (on the effect of instructions, see Bencini & Goldberg, 2000), thus we cannot say how sorting would occur in the absence of training. Nevertheless, this method is commonly used to understand how learners conceptualize potentially ambiguous stimuli (see e.g., Hommel, Alonso & Fuentes, 2003;Chambers, Onishi & Fisher, 2010). When participants are trained using one type of stimuli (e.g., transparent one--, two--and three--argument pictures) and then tested with very different stimuli (e.g., light--verb constructions), we can learn how they generalize their training.…”
Section: Discussionmentioning
confidence: 99%
“…First, we explicitly trained participants to pay attention to semantic roles and provided extensive instructions (on the effect of instructions, see Bencini & Goldberg, 2000), thus we cannot say how sorting would occur in the absence of training. Nevertheless, this method is commonly used to understand how learners conceptualize potentially ambiguous stimuli (see e.g., Hommel, Alonso & Fuentes, 2003;Chambers, Onishi & Fisher, 2010). When participants are trained using one type of stimuli (e.g., transparent one--, two--and three--argument pictures) and then tested with very different stimuli (e.g., light--verb constructions), we can learn how they generalize their training.…”
Section: Discussionmentioning
confidence: 99%
“…Previous phonotactic learning experiments (e.g., Chambers, Onishi, & Fisher, 2003, 2010, 2011; Dell, Reed, Adams, & Meyer, 2000; Goldrick & Larson, 2008; Onishi, Chambers, & Fisher, 2002; Seidl, Cristià, Bernard, & Onishi, 2009; Warker, 2013; Warker & Dell, 2006) have described phonotactic patterns at the level of the syllable, but they did not directly test whether representations were at the syllable or word level (since most have used one-syllable, consonant-vowel-consonant or CVC items). The current experiments seek evidence that phonotactic knowledge can be represented at the level of the syllable (or syllable-sized unit), independent of the word, by examining whether syllable-level patterns generalize across word position and word structure, thus asking whether an onset is an onset and a coda is a coda regardless of word structure and position.…”
Section: (3) Evidence Suggesting the Word As A Possible Unit Of Reprementioning
confidence: 99%
“…For example, it has been shown that learners induce constraints on consonants across different vowel contexts, suggesting that consonants and vowels are processed independently (Bonatti et al, 2005;Chambers et al, 2010). In addition, several studies indicate that patterns of natural classes are easier to learn than patterns of arbitrary classes of segments (Cristià & Seidl, 2008;Finley & Badecker, 2009;Seidl & Buckley, 2005).…”
Section: Introductionmentioning
confidence: 99%